Copper nanoclusters modified molybdenum disulfide quantum dots probe for sensitive detection of tetracycline - Xiaoxue Tang; Haonan Chi; Zijian Jia; Jingxue Lv; Yuguang Lv; Jiang Wu (Sensing and Bio-Sensing Research, 2024)
By combining molybdenum disulfide quantum dots (MoS2 QDs) synthesized using a facile hydrothermal method with copper nanoclusters (Cu NCs), copper-ion-modified molybdenum disulfide probes (Cu-MoS2 QDs) were obtained, enabling sensitive detection and specific recognition of tetracycline (TET). The synthesized probes were characterized using techniques such as fourier-transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), and scanning electron microscopy (SEM). The fluorescence values of the probes and TET after their reaction at different concentrations were used to calculate a detection limit of 30 nM for the synthesized probes. The recovery rate of actual samples reached a high value of 95.70%, with a relative standard deviation below 2.00%, demonstrating excellent accuracy and precision. The probe exhibited high selectivity towards TET. The accuracy is maximized when the concentration of the probe is 4.50 × 10−5 mol/L, indicating enhanced performance of the molybdenum disulfide probe after copper ion modification and obtaining favorable detection outcomes. This probe holds great potential in enhancing the safety of animal-derived food, ensuring public health, and preserving water resources.